(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper explores the fundamental methods of using Artificial Intelligence (AI) to enhance English Language Teaching (ELT). It examines the benefits of AI in personalizing learning, providing interactive and engaging experiences, and automating assessment processes. The paper discusses key AIpowered techniques such as speech recognition, chatbots, automated text analysis, and personalized learning programs. It also addresses the challenges associated with AI implementation, including technical issues, data privacy concerns, and the need for teacher training. Finally, the paper analyzes the future prospects of AI in ELT, highlighting emerging technologies and potential applications that could transform the way English is learned and taught. The findings suggest that AI has the potential to revolutionize ELT, but careful consideration must be given to ethical implications and the need for human-centered approaches.